"Books, physical spaces, rules, people": A holistic analysis of young Chinese children's perceptions of public libraries. (June 2022) - Wang, Pianran; Xu, Jianhua; Sturm, Brian W.; Kang, Qi; Wu, Yingying
Young children's perceptions of library services are often ignored when providing library services to this group. In order to reveal young children's perceptions, grounded theory technique was used to analyze the interview data from 92 young Chinese children. The authors first proposed an integrated model of young children's perceptions of Chinese public libraries, including the elements of books, physical spaces, rules, and people. Subsequently, the model is compared to the adult experts' perspectives, revealing that young children could perceive all the experts' proposed services and functions. Besides, they could perceive rules in libraries. Furthermore, young children were able to convert the abstract library classification index system to perceptible clues. The findings could be used to improve library services to accurately conform to young children's perspectives.